Perbedaan Stres Akademik Ditinjau dari Jenis Kelamin dan Aktivitas pada Mahasiswa - Vita Ayu Lestari; Tazkiyatun Nafsi; Lucky Purwantini (Universitas Palangka Raya, 2026)
Academic stress is a common issue faced by university students due to high academic and nonacademic demands. This study aimed to identify differences in academic stress levels based on gender and student activity. A comparative quantitative approach was used, involving 1,062 diploma and undergraduate students in Indonesia selected through convenience sampling. Data were collected using the Educational Stress Scale for Adolescents (ESSA) through an online questionnaire in April 2026. Normality test results showed the data were not normally distributed, so nonparametric tests were used for hypothesis testing. The Friedman test showed a significant difference in mean rank between gender and student activity variables (p = 0.001), supporting the research hypothesis. Mann-Whitney and Kruskal-Wallis tests on other demographic characteristics also showed significant differences in academic stress based on scholarship status, migrant status, activity type, semester, cumulative grade point average, living arrangement, and post-graduation orientation. Students who focused solely on coursework tended to report the highest academic stress, while students who studied while running a business reported the lowest. These findings confirm that academic stress is multifactorial and offer implications for universities to design student wellbeing programs that account for diverse demographic characteristics.